FAKTOR - FAKTOR YANG MENYEBABKAN KETIDAK PUASAN PASIEN BPJS (JAMKESDA) TERHADAP PELAYANAN BPJS DI POLIKLINIK RSUD TALUK KUANTAN TAHUN 2017 - Nany Librianty (Universitas Pahlawan, 2018)
JAMKESMAS is a Community Health Insurance initiated by former health minister Siti Fadilah Supari, initially pioneering the implementation of a free health service program for the poor. The government began running a free health care program for the poor in 2005. At that time the program was called poor community health insurance (Askeskin). This study uses a type of analytical design with cross sectional approach. Data collection and interviews using questionnaires. Data is analyzed by univariate and bivariate. This research was conducted at Taluk Kuantan General Hospital with a sample of 57 people taking treatment using a BPJS card (JAMKESDA), the results showed a relationship of referral system factors with BPJS service satisfaction, a relationship between speed factor responses and BPJS service satisfaction, a relationship between drug cost factors with satisfaction with BPJS services. Conclusions there is a meaningful relationship between the referral system, the speed of responding, the cost of the drug with satisfaction of BPJS services (JAMKESDA) in the Polyclinic of Taluk Kuantan Hospital in 2017, it is expected that Teluk Kuantan Hospital provides information to respondents regarding services using BPJS.